Beyond biodiversity conservation - Mohd Nazip Suratman (Research management institute publication series : biodiversity, 2014)
Based on the vital attributes of biodiversity and its importance of conservation, this book conveys important messages of what it takes for surviving biodiversity amidst degradation. [This book] is a platform for future planning and policy making, which is a melting port of future prescription to develop a silver bullet in treating the threatening biodiversity.